2018
DOI: 10.1002/celc.201800883
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining P2‐Na0.56[Ni0.1Co0.1Mn0.8]O2 Cathode Materials for Sodium‐Ion Batteries by using a Co‐precipitation Method

Abstract: For the sake of achieving the practical application of sodium‐ion batteries, extensive efforts have been made to improve the electrochemical performance of cathode materials. A simple co‐precipitation route is successfully developed to synthesize nanowires of transition metal hydroxides through a sodium peroxide pouring process instead of the traditional sodium hydroxide dropping approach. After a subsequent annealing process, a well‐crystallized P2‐Na0.56[Ni0.1Co0.1Mn0.8]O2 layered cathode material is obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…1 Mn 0 . 8 O 2 (NaNCM118) was selected as a model CAM because of its reversibility up to ∼4.5 V (vs Na/Na + ) or higher, 72,73 which is consistent with the cell test result of NaNCM118 cathodes using conventional liquid electrolytes (Figure S13). The crystal structure of NaNCM118 is shown in Figure S14 and Table S6.…”
mentioning
confidence: 59%
“…1 Mn 0 . 8 O 2 (NaNCM118) was selected as a model CAM because of its reversibility up to ∼4.5 V (vs Na/Na + ) or higher, 72,73 which is consistent with the cell test result of NaNCM118 cathodes using conventional liquid electrolytes (Figure S13). The crystal structure of NaNCM118 is shown in Figure S14 and Table S6.…”
mentioning
confidence: 59%
“…The precursors are simply sodiated with NaOH or Na 2 CO 3 by calcining at generally higher temperatures than that for Li­(Ni a Mn b Co c )­O 2 (LiNMC) to facilitate crystal structure formation and sodium diffusion into the particles. While not all of these NaNMC materials result in good morphology, many groups have successfully synthesized particles with morphology similar to that of typical LiNMC particles. , Notably, all of the publications that report good NaNMC morphology mention the use of a stirred tank reactor for particle synthesis, while many of the other publications use smaller-scale setups, such as beakers. It is, therefore, clear that synthesizing NaNMC particles by the coprecipitation method is not significantly more challenging than synthesizing LiNMC.…”
Section: History Of Coprecipitationmentioning
confidence: 99%
“…The ability to use hydroxide coprecipitation to synthesize sodium-based cathode materials is, therefore, necessary with respect to both utilizing existing infrastructure and controlling particle morphology. Despite this, the majority of reported sodium-based layered-oxide work does not utilize coprecipitation techniques, or desirable particle morphology is rarely achieved when hydroxide coprecipitation has been employed. The most common synthesis methods of solid-state and sol–gel synthesis produce highly irregular, agglomerated particles with poor tap density and high surface area. Performance obtained with these materials does not accurately reflect optimal performance, thereby hampering the progress in the sodium-ion battery field.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the materials obtained after delithiation at 1.5 and 2.0 V, the diffraction peak associated with the pristine material completely disappeared, and a diffraction peak of δ-MnO 2 crystal type was observed. 46 This suggested that the crystal structure of the pristine material was completely destroyed and transformed. 41 The four materials all exhibited PVDF diffraction peaks at 2θ = 26.5°.…”
Section: Physical Characterizations Of the Delithiated Materialsmentioning
confidence: 99%